LIVED EXPERIENCES OF HEALTH INFORMATION PROCESSING AMONG TYPE 2 DIABETES MELLITUS PATIENTS IN BANDUNG CITY: A PHENOMENOLOGICAL STUDY - Solihin, Olih; rantona, Safutra; Sovianti, Rina; Kurniawan, Rio (International Archives of Medical Sciences and Public Health, 2026)
Health literacy plays an essential role in effective self-management of type 2 diabetes mellitus (T2DM). There is insufficient research in the qualitative literature on health information processing among Indonesian urban populations seeking primary healthcare. This exploratory phenomenological study aimed to explore the lived experience of seven adults with T2DM in Bandung, Indonesia, in relation to health information processing and barriers to understanding. The data were collectedvia in-depth interviews (December 2025-January 2026) and analyzed using reflexive thematic analysis. Considering the sample size of seven individuals purposefully selected, the results can be considered preliminary and non-generalizable. Four main themes arose from the analysis: (1) varied sources of health information and variable abilities to evaluate health information sources; (2) comprehension barriers due to technical medical language without sufficient context; (3) barriers to patient-health worker communication because of structural, linguistic, and cultural factors; and (4) various influences of digital media and peer socialization on health behavior. It was identified that health literacy is a continuum process, which depends not only on personal characteristics of patients but also on the communicative setting of medical consultations. Recommended actions for addressing the problem include health workers’ training on patient-centered communication (e.g., teach-back technique), development of online resources